Elevated levels of arachidonic acid metabolites in follicular fluid of PCOS patients. Issue 2 (February 2020) - Li, Shengxian; Qi, Jia; Tao, Yongzhen; Zhu, Qinling; Huang, Rong; Liao, Yu; Yue, Jiang; Liu, Wei; Zhao, Hanting; Yin, Huiyong; Sun, Yun
Abstract : Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in reproductive-age women usually accompanied by lipid metabolic disorders. However, it remains unknown whether arachidonic acid (AA) and its metabolites in follicular fluid (FF) were altered in PCOS patients. This study was intended to measure the levels of AA and its metabolites in the FF of non-obese PCOS patients that underwent in vitro fertilization (IVF) and to explore the possible causes of the alterations. Thirty-nine non-obese women with PCOS and 30 non-obese women without PCOS were enrolled. AA and its metabolites were measured by liquid chromatography-mass spectrometry. The levels of AA metabolites generated via cyclooxygenase-2 (COX-2) pathway and cytochrome P450 epoxygenase pathway but not lipoxygenase (LOX) pathway were significantly higher in the FF of PCOS patients. The metabolites generated via COX-2 pathway were significantly correlated with levels of testosterone and fasting insulin in serum. The in vitro study further demonstrated that insulin but not testosterone could promote the IL-1β and hCG-induced COX-2 expression and prostaglandin E2 (PGE2 ) secretion in primary human granulosa cells. In conclusion, there was an elevation in AA metabolites in FF of PCOS patients. Insulin played a pivotal role in the increased AA metabolites generated via COX-2, which could be interpreted as another novel molecular pathophysiological mechanism of PCOS.